Developing Statistical Literacy Through Tasks: An Analysis of Secondary School Mathematics Textbooks - Setiawan, Ezra Putranda; Sukoco, Heru; Agustyani, Anggit Reviana Dewi (Mathematics Education Journal, 2023)
Statistical literacy is an essential competence that people must face in the era of big data and Society 5.0. In Indonesia and several countries, statistics is taught as a list of competencies in mathematics subject in primary and secondary schools. This study aimed to identify whether statistical tasks in higher secondary school mathematics textbooks support statistical literacy. The qualitative data were collected via deductive content analysis, with a specific framework, toward five Compulsory Mathematics textbooks used in Indonesia. We found that statistical exercises and problems in these textbooks were dominated by data analysis type, emphasizing calculating statistics from raw data and its modification. Regarding data visualization, almost all textbooks introduced the histogram and ogive, while some also introduced the boxplot, stem-and-leaf plot, and dot plot. Improvement could be made by adding more exercises and problems related to the interpretation of statistics, evaluation of statistical results, and comparison of statistics from several data groups. DOI: https://doi.org/10.22342/jpm.17.2.2023.247-264